Justification: The Dilemma of the Sixteenth Century - Tavard, George H. (Philosophy & theology, 1987)
This article and its sequel illustrate the thesis that oblivion of the doctrine of justification and liturgical-eucharistic decadence went together in the middle ages. The ensuing contradictions led directly to the Reformation. Luther recovered the doctrine of justification as he tried to answer the question, how do sinners become just in God’s eyes? But his liturgical reforms were inspired by a medieval theology which made it impossible for him to restore the patristic insight into liturgy and the eucharistic mystery. The council of Trent went a long way toward meeting Luther on justification, but did not attempt to do so in its liturgical reforms, which established the framework for the Counter-Reformation. Thus Catholic and Lutheran differences are based on misunderstandings no less than on different doctrinal stresses.